Developing a Policy Model to Enhance Local Council Capacity in Budget Management and Council Meeting Procedures in Thailand’s Southern Border Provinces - Ceahael, Chiya (Al-HIKMAH Journal, 2026)
This research aimed to examine the problems and competency gaps of local council chairpersons and members in budget management and council meeting procedures, develop an action learning process, and synthesize a policy model for enhancing local councils toward competency-based local government organizations in Thailand’s southern border provinces. The study employed a research and development approach based on work-based practice, problem reflection, collaborative learning, and the synthesis of policy recommendations. The target groups included local council chairpersons, vice chairpersons, local council members, local government personnel, and relevant supervisory agencies. The findings revealed that local council chairpersons and members still faced competency gaps in laws, council meeting regulations, budget management, budget amendment procedures, and the oversight of local executives. These gaps created institutional risks, including incorrect meeting procedures, inappropriate budget consideration processes, unclear communication, and information asymmetry among local executives, council members, and citizens. Therefore, capacity development should not be limited to short-term training. Instead, it should be designed as a continuous learning system that integrates action learning, professional learning communities, and mentorship. Such a process enables local actors to learn from real problems, engage in reflection, and jointly develop practical solutions. The proposed policy model consists of five key components: competency gap assessment, contextualized curriculum and development tools, action-based training, PLC and mentorship systems, and monitoring and evaluation. The model can serve as a guideline for strengthening local council capacity, reducing institutional risks, promoting good governance, and enhancing public trust in local government organizations within multicultural contexts.